Advance care planning readiness among community-dwelling older adults and the influencing factors: a scoping review - Fang Gao; Ping Lei Chui; Chong Chin Che; Li Xiao; Qin Zhang (BMC Palliative Care)
Abstract Background Advance care planning (ACP) is pivotal in mitigating end-of-life suffering and ensuring healthcare congruence with the values of older adults and dignity in death. Despite its paramount importance, the current readiness for ACP among community-dwelling older adults and the intricate influencing factors have yet to be explored. Objective To review the literature focusing on ACP readiness among community-dwelling older adults and the influencing factors. Methods A scoping review conducted using the Arksey and O’Malley (2005) framework. Electronic databases (PubMed, CINAHL, Cochrane, Web of Science, PsycINFO), as well as grey literature databases (OpenGrey and GreyLit.org) were searched to identify studies published in English between January 2012 and March 2023. Results 19 studies were selected, comprising 3 qualitative, 13 quantitative, 2 mixed-methods, and 1 review article. The study evaluated the readiness of older adults for ACP by examining their knowledge and attitudes. It categorizes influencing factors into intrinsic and extrinsic levels. This review revealed that the knowledge about ACP among older adults across all settings was limited. However, they had positive attitudes toward it. In addition, intrinsic factors including sociodemographic characteristics, psychological factors, and family relationships, along with extrinsic factors including health care professionals’ attitudes and experience, as well as policies and laws, influenced the ACP readiness among older adults. Conclusions This study established the groundwork for future ACP intervention trials, providing a theoretical framework to guide their design and implementation. operationalization.